Relation between extracellular Chemistry and Patient Outcome for Severe Traumatic Brain Injury within the First 24 hours: A Microdialysis Study - Igarashi, Yutaka; Yokobori, Shoji; Onda, Hidetaka; Masuno, Tomohiko; Yokota, Hiroyuki (Indian Journal of Neurotrauma, 2017)
Object Many studies have reported that extracellular chemistry is related to the outcome of patients with traumatic brain injury (TBI). No study has reported that extracellular chemistry predicts outcome in less than 3 days. Moreover, in other studies, both focal brain and diffuse brain injuries have been often discussed. The authors focused on the relationship between extracellular chemistry in a shorter period and the outcome of patients with focal brain injury.Methods By using intracerebral microdialysis monitoring, extracellular fluid concentrations of glucose, lactate, glycerol, glutamate, lactate/pyruvate (L/P), and lactate/glucose (L/G) were determined in 30 patients with severe TBI for initial 24 hours. The results were analyzed between favorable and unfavorable, and between survival and mortality.Results The medians of glycerol and L/P in the favorable group were significantly lower than those in the unfavorable group (124 µmol/L vs. 808 µmol/L, p = 0.002; 31 vs. 48, p = 0.021, respectively). All parameters apart from glutamate differed significantly between the survival and mortality groups (glucose, 25 mmol/L vs. 77 mmol/L, p = 0.035; lactate, 38 mmol/L vs. 73 mmol/L, p = 0.018; glycerol, 168 µmol/L vs. 1462 µmol/L, p = 0.002; glutamate, 14 µmol/L vs. 95 µmol/L, p = 0.019; L/P, 32 vs. 124, p < 0.001; L/G, 1.46 vs. 4.52, p = 0.004).Conclusion Cerebral extracellular glycerol and L/P was the most reliable predictor of outcomes in patients with focal brain injury and can discriminate between favorable and unfavorable outcomes for the first 24 hours, using the threshold of 200 and 40, respectively.
Keywords: microdialysis; traumatic brain injury; cerebral extracellular chemistry; lactate/pyruvate; glycerol